2013
DOI: 10.1037/a0033452
|View full text |Cite
|
Sign up to set email alerts
|

Advancement staff and alumni advocates: Cultivating LGBTQ alumni by promoting individual and community uplift.

Abstract: Using a constructivist case-study analysis, we explore philanthropy toward higher education among lesbian, gay, bisexual, transgender, and queer (LGBTQ) alumni, examining the role of advancement staff and alumni advocates in engaging LGBTQ alumni to promote individual and community uplift. Data come from focus groups with 37 advancement staff and 23 LGBTQ alumni at three higher education institutions. Findings reveal the importance of advancement staff and alumni in promoting LGBTQ alumni philanthropy. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Among their discoveries, the report indicated that LGBTQ respondents experienced significantly more amounts of harassment and discrimination than their heterosexual and cisgender peers while on campus and leading to negative feelings regarding their alma maters. Furthermore, few campuses make thoughtful efforts to reach out to the LGBTQ communities to gain insights into their philanthropic giving (Garvey & Drezner, 2013;Scanlan & Abrahams, 2002).…”
Section: Factors Related To Philanthropy Within Lgbtq Communitiesmentioning
confidence: 99%
“…Among their discoveries, the report indicated that LGBTQ respondents experienced significantly more amounts of harassment and discrimination than their heterosexual and cisgender peers while on campus and leading to negative feelings regarding their alma maters. Furthermore, few campuses make thoughtful efforts to reach out to the LGBTQ communities to gain insights into their philanthropic giving (Garvey & Drezner, 2013;Scanlan & Abrahams, 2002).…”
Section: Factors Related To Philanthropy Within Lgbtq Communitiesmentioning
confidence: 99%
“…The connection between a positive student experience and charitable giving among non-traditional donors has gained the interest of prominent scholars (e.g., Clotfelter, 2003;Gasman & Anderson-Thompkins, 2003;Gasman & Bowman, 2013b), and a handful of colleges and universities across the country (e.g., Columbia University, University of Pennsylvania, Cornell University). One population of alumni that has gained more attention recently is alumni that identify as lesbian, gay, bisexual, transgender, and queer (LGBTQ) (Garvey & Drezner, 2013a;Garvey & Drezner, 2013b). Despite this attention, research focused specifically on LGBTQ college alumni remains significantly understudied in the realm of philanthropy (Garvey & Drezner, 2013b).…”
mentioning
confidence: 99%
“…It is important for the institution to determine if the welcoming environment and sense of home are the same for multicultural students. If the institution and the alumni association are seeking philanthropic support from young alumni from diverse backgrounds, learning about the student experiences of these populations is important (Garvey & Drezner, 2013;Harper & Quaye, 2009).…”
Section: Provide Students With Meaningful Experiences That Make Them mentioning
confidence: 99%
“…Alumni associations may also benefit by examining who is currently involved in philanthropically supporting the institution, and their current practices for recruiting membership on its young alumni council. According to Garvey and Drezner (2013), many institutions are now working to philanthropically engage more diverse alumni populations, but they are finding it difficult to create connections because they have felt ignored by their alma maters. They suggest that finding means for "cultivating and sustaining relationships among underrepresented minorities is critical" (p. 200).…”
Section: Examine Inclusivitymentioning
confidence: 99%
See 1 more Smart Citation